Dynamic simulation and modeling of the motion modes produced during the 3D controlled manipulation of biological micro/nanoparticles based on the AFM. (7th August 2015) - Saraee, Mahdieh B.; Korayem, Moharam H.
Abstract: Determining the motion modes and the exact position of a particle displaced during the manipulation process is of special importance. This issue becomes even more important when the studied particles are biological micro/nanoparticles and the goals of manipulation are the transfer of these particles within body cells, repair of cancerous cells and the delivery of medication to damaged cells. However, due to the delicate nature of biological nanoparticles and their higher vulnerability, by obtaining the necessary force of manipulation for the considered motion mode, we can prevent the sample from interlocking with or sticking to the substrate because of applying a weak force or avoid damaging the sample due to the exertion of excessive force. In this paper, the dynamic behaviors and the motion modes of biological micro/nanoparticles such as DNA, yeast, platelet and bacteria due to the 3D manipulation effect have been investigated. Since the above nanoparticles generally have a cylindrical shape, the cylindrical contact models have been employed in an attempt to more precisely model the forces exerted on the nanoparticle during the manipulation process. Also, this investigation has performed a comprehensive modeling and simulation of all the possible motion modes in 3D manipulation by taking into account the eccentricity of the applied load on the biological nanoparticle. The obtained results indicate that unlike the macroscopic scale, the sliding of nanoparticle on substrate in nano-scale takes place sooner than the other motion modes and that the spinning about the vertical and transverse axes and the rolling of nanoparticle occur later than the other motion modes. The simulation results also indicate that the applied force necessary for the onset of nanoparticle movement and the resulting motion mode depend on the size and aspect ratio of the nanoparticle. Graphical abstract: Highlights: A dynamic model is proposed for the 3-D manipulation of bionanoparticle. The cylindrical contact model is considered for contact between nanoparticle and substrate, which is closer to their real geometry. Seven motion modes are produced and simulated during 3-D manipulation. For four different biological nanoparticles, effective parameters in different motion modes have been studied. The sliding of nanoparticle on substrate in nano-scale takes place sooner than the other motion modes and it is unlike to the macroscopic scale.